Potential health promotion benefits of lipid testing for all patients presenting with chest pain to an emergency department. Issue 1 (22nd December 2005) - Elder, C V; Kerr, D; Davey, R X; Kelly, A-M
Abstract : Objectives: To establish the prevalence of previously undiagnosed dyslipidaemia in patients presenting to the emergency department (ED) with non-traumatic chest pain and, more particularly, the prevalence in the subgroup which was discharged home from the ED, the group that traditionally would not have received a lipid test. Methods: Prospective, observational study of adult patients presenting to an ED with non-traumatic chest pain as the presenting complaint. Results: A total of 185 eligible patients underwent lipid testing during their presentation: 96 in the ED and 89 in the wards. Overall 61% (n = 112) of patients had at least one abnormal lipid level. Of patients discharged from the ED, 62% had at least one abnormal lipid level. Conclusions: A moderate, but useful, increase in detection rates of dyslipidaemia is possible if lipid testing is offered to all patients presenting with chest pain, and not just to those who are admitted to wards for further investigation and management of suspected acute coronary syndromes. Testing of this group should be considered as a health promotion initiative in the ED, with appropriate follow up in the community.